The Qualitative Vision for Psychology : An Invitation to a Human Science Approach - Fischer, Constance T., 1938-; Laubscher, Leswin; Brooke, Roger, 1953- (Book collections on Project MUSE., 2016)
"This volume, edited by three leading proponents and practitioners of human science psychology, serves as an invitation to readers new to this approach while also renewing that invitation to those who have long embraced and advanced research in the field from this perspective. It is a timely and important invitation. In 2009, the American Psychological Association declared psychology to be a core STEM (science, technology, engineering, mathematics) discipline and advocated the teaching and practice of psychology with this natural science understanding in mind, but in 2014 further reaffirmed alternative methods by adding a new journal, Qualitative Psychology. The varied essays in this volume, certainly, bolster the view that a purely STEM-centered vision would ignore much about the very experience of being human. In fact, it would be dangerous to rely solely on the methods of the natural sciences to study human beings, who operate in the realm of meanings, lived experience, and complex and complicated relationships with self and others. We create societies and belief systems, orient ourselves in time, experience beauty and pain. The Qualitative Vision for Psychology: An Invitation to a Human Science Approach argues that because we have aspects that are distinctly and uniquely human -- we are not rats, hydrogen, or rocks, for example -- this necessitates a distinctly human science, one that regards persons as humans rather than objects of study. The laws and formulas of the natural sciences simply do not take into account that particularly human way of being in the world. There are few comprehensive books on psychology conceived as a human science, even though it has a long history with roots in phenomenology, existentialism, psychoanalysis, humanistic psychology, and hermeneutics. In recent years, as these essays discuss, the field has been transformed through its contact with feminism, critical historical analysis, and deconstruction, and it has continued to examine new challenges. Further, we see here its specific applicability to issues as diverse as empathy, cultural history, apartheid, sexual assault, fetishes, and our natural environment."--